Developmental ontogeny of prolactin and its receptor in fish - Power, Deborah (2014)
Prolactin (PRL) is a member of a family of structurally similar proteins which includes growth hormone (GH) and somatolactin (SL) in teleost Wsh. The genes encoding these proteins are expressed principally in the pituitary gland and sequence analysis reveals they share considerable similarity. GH, PRL, and SL bring about their physiological action by binding to speciWc receptors localised in the membrane of cells in target tissue. The PRL receptor (PRLR) and GH receptor (GHR) have been identiWed in a number of teleosts but the SL receptor remains to be characterised. On hormone binding, receptors dimerise, and signal transduction occurs via the JAK/STAT signalling pathway. The principal action of PRL in Wsh is freshwater osmoregulation, although it has also been implicated in reproduction, behaviour, growth, and immunoregulation. The role of PRL in early development and metamorphosis is well established, respectively, in mammals and amphibians, although its role in Wsh is not so well known. Studies have shown that PRL mRNA and protein are restricted to the developing pituitary gland in Wsh embryos and larvae. PRLR mRNA and protein is also present in Wsh embryos and has a widespread tissue distribution in larvae. The levels of PRLR and PRL mRNA vary throughout embryonic and early larval development. The potential role of PRL in Wsh embryos and larvae is considered in relation to their physiological status.